Political Policy Analysis of the National Education Budget In Islamic Education Studies - Firman Mansir (Postgraduate Program Magister Pendidikan Agama Islam, 2019)
This research reviews about national education budget in the study of Islamic education policy. The federal education budget is part of the political education policy in Indonesia. The politic of education budget can be realized through systems made in a country. Government policy regarding education budget allocation of 20% is by the mandate of the 1945 constitution as included in the Draft State Revenue and Expenditure Budget (RAPBN). It is explained explicitly in the Statute of National Education System No.20 Year 2003 in article 49. This policy also becomes a lantern which can ease the economic burden of the poor to send their children to school because they have received funding from the government. However, the realization of the budget education of 20% may not be disbursed according to the benchmark percentage. Besides, there is Islamic education which has its institution in managing educational practices. This research was qualitative by collecting literature data from various primary and secondary references. Politic in education budget can make people more eager if all policy can protect other educational components, especially in the realm of Islamic education.Penelitian ini mengulas tentang anggaran pendidikan nasional dalam studi kebijakan pendidikan Islam. Anggaran pendidikan federal adalah bagian dari kebijakan pendidikan politik di Indonesia. Politik anggaran pendidikan dapat diwujudkan melalui sistem yang dibuat di suatu negara. Kebijakan pemerintah tentang alokasi anggaran pendidikan sebesar 20% adalah dengan mandat UUD 1945 sebagaimana tercantum dalam Rancangan Anggaran Pendapatan dan Belanja Negara (RAPBN). Hal ini dijelaskan secara eksplisit dalam Undang-Undang Sistem Pendidikan Nasional No.20 Tahun 2003 dalam pasal 49. Kebijakan ini juga menjadi lentera yang dapat meringankan beban ekonomi orang miskin untuk menyekolahkan anak-anak mereka karena mereka telah menerima dana dari pemerintah. Namun, realisasi anggaran pendidikan 20% tidak dapat dicairkan sesuai dengan persentase patokan. Selain itu, ada pendidikan Islam yang memiliki institusi dalam mengelola praktik pendidikan. Penelitian ini adalah kualitatif dengan mengumpulkan data literatur dari berbagai referensi primer dan sekunder. Politik dalam anggaran pendidikan dapat membuat orang lebih bersemangat jika semua kebijakan dapat melindungi komponen pendidikan lainnya, terutama di bidang pendidikan Islam.